2019
DOI: 10.1111/conl.12639
|View full text |Cite
|
Sign up to set email alerts
|

A risk‐based forecast of extreme mortality events in small cetaceans: Using stranding data to inform conservation practice

Abstract: Effective conservation requires monitoring and pro‐active risk assessments. We studied the effects of at‐sea mortality events (ASMEs) in marine mammals over two decades (1990–2012) and built a risk‐based indicator for the European Union's Marine Strategy Framework Directive. Strandings of harbor porpoises (Phocoena phocoena), short‐beaked common dolphins (Delphinus delphis), and striped dolphins (Stenella coeruleoalba) along French coastlines were analyzed using Extreme Value Theory (EVT). EVT operationalizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…No significant seasonal pattern in number of strandings was found among overall records, in line with Bouchard et al (2019), who also showed low seasonality of strandings in this species, interpreted as an indicator of constant pressures across the seasons. However, along the CS coast, which is the only area with no local stranding team operating, there were significant seasonal differences.…”
Section: Diet Analysissupporting
confidence: 79%
“…No significant seasonal pattern in number of strandings was found among overall records, in line with Bouchard et al (2019), who also showed low seasonality of strandings in this species, interpreted as an indicator of constant pressures across the seasons. However, along the CS coast, which is the only area with no local stranding team operating, there were significant seasonal differences.…”
Section: Diet Analysissupporting
confidence: 79%
“…The seasonality is seen as a bimodal distribution with peaks around March and August. Seasonality is also seen for the New Zealand mass strandings as shown in Figure 3c (see also Bouchard et al, 2019, for seasonality in a French stranding data set not analyzed here). Seasonal dependence of mass stranding and geomagnetic data will give rise to a seasonally varying statistical association, even in the absence of causal connection.…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 64%
“…During major solar storm events, interplanetary disturbances can generate major changes in the Earth's near‐space electric current systems and those changes cause geomagnetic field variations at times scales varying from seconds to days. We refer to these magnetic field variations as “geomagnetic storms.” Interaction with fisheries through bycatch (e.g., Bouchard et al, 2019). Active sonars utilized in military activities (e.g., Southall et al, 2013).…”
Section: Introductionmentioning
confidence: 99%